THE IMPORTANCE OF THE FATHER'S EDUCATIONAL FUNCTION IN THE FORMATION OF THE EMOTIONAL SPHERE OF A PRESCHOOL CHILD - Sokolova, Antonina A.; Eliseeva, Natalia D. (Russian Journal of Education and Psychology, 2024)
Background. The present study was aimed at studying the influence of the father's educational functions on the development of the emotional sphere of a preschool child. In modern society, there are fewer and fewer conditions favorable for the full emotional development of a child, and the deficit of communication between a child and adults, in particular with his father, is increasing. Purpose. The study of the significance of the educational function of the father in the formation of the emotional sphere of a preschool child. Materials and methods. 112 people participated in the study: 56 children and 56 mothers. The method for self-assessment "Ladder" was used; a method for determining the features of the emotional state "Steam Train"; a graphic method for identifying the state of the emotional sphere of the child "Cactus"; a method for identifying the features of intra-family relationships "Family drawing"; a test "Geometric figure" (association with the father) and a questionnaire, aimed at revealing mothers' ideas about the educational functions of the father. Results. With the active participation of fathers in the upbringing of a child, psychological closeness, positive emotional attachment are expressed, there are uniform requirements of parents on parenting issues. The inclusion of fathers in the process of raising a child has a positive effect on his emotional state. The active participation of fathers in the upbringing of a child has a positive effect: on the level of self-esteem, the emotional sphere of the child, the level of thinking. In families where fathers do not take part in the upbringing of a child, children have increased egocentrism, aggressiveness, impulsivity, secrecy, optimism and anxiety, they do not seek home protection at home. EDN: UVIRTH